PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN VULVA HYGIENE PADA REMAJA PUTRI - Fauziah, Dewi Lailatul; Retnaningsih, Reny; Indriati, Ina (Universitas Pesantren Tinggi Darul Ulum, 2024)
One of the reproductive health problems often experienced by young women is caused by not knowing how to perform vulva hygiene. Vulva hygiene is maintaining the cleanliness of the external genital organs (Ernawati, 2023). This research aims to determine whether there is an influence of health education through video media on the level of knowledge in class VII teenage girls at MTs Miftahul Ulum Sumberwringin Klakah Lumajang. This research uses a pre-experimental design with a one group pre post-test design method. Measuring the level of knowledge uses a questionnaire. Statistical tests use the Wilcoxon test. The research was conducted in April. The research sample was taken using a non-probability sampling technique (purposive sampling), obtaining 24 female students as respondents. With the Wilcoxon signed test using SPSS, it was found that p-value = 0,000 < 0.05. it can be concluded that there is an influence of health education through video media on the level of knowledge of respondents. The results of the study support the idea that there is an increase in knowledge about vulva hygiene after being given health education through video media to teenage girls in class VII MTs Miftahul Ulum Sumberwringin Klakah Lumajang. Keiywords: Adoleisceints, Heialth Eiducation, Leiveil of Knowleidgei, Video.